Modification method of nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material
Through the nitrogen-doped carbon double coating modification method, the problem of insufficient specific capacity and rate performance of sodium vanadium phosphate cathode materials in sodium-ion batteries has been solved, and the material's high performance and good cycle stability at high rates have been achieved. .
Patent Information
- Application Number
- CN202311185860.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-09-14
AI Technical Summary
The actual specific capacity of sodium vanadium phosphate (NVP) cathode material in sodium ion batteries is relatively low and the rate performance is not ideal, which limits its application in sodium ion batteries.
Through the nitrogen-doped carbon double-coating modification method, the nitrogen-doped carbon double-coated sodium vanadium phosphate (NVP/C/NC-TRI) cathode material is formed, which improves the electronic conductivity and ion diffusion rate of the material.
It significantly improves the performance and cycle stability of the cathode material at high rates, improves the specific capacity and rate performance of sodium-ion batteries, and has good application prospects.
Smart Images

Figure CN117566712B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials for sodium ion batteries, and in particular relates to a modification method for a nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material. Background Art
[0002] Lithium-ion batteries have dominated the power battery market with their high energy density, high specific capacity and long cycle life, but the global lithium resources are unevenly distributed and prices are rising, making it difficult to fully support large-scale energy storage and electric vehicles. Sodium-ion batteries (SIBs) are similar to lithium-ion batteries in electrochemical properties and working mechanisms, and have the advantages of abundant raw material reserves, low cost, safety and environmental protection. They are expected to become the next generation of secondary batteries to replace lithium-ion batteries and are a promising grid-scale energy storage technology.
[0003] Sodium vanadium phosphate [Na3V2(PO4)3, NVP] cathode material has the advantages of stable three-dimensional framework structure, high energy density (400Wh / kg), high theoretical specific capacity (117.6mA·h / g) and high operating voltage (about 3.4V). It has become a hot spot in the research of sodium ion battery cathode materials in recent years.
[0004] However, NVP's low electronic conductivity and slow ion diffusion rate result in low actual specific capacity and unsatisfactory rate performance, which hinders its further development. To this end, researchers optimized the synthesis process of NVP and modified it by methods such as conductive material coating, ion doping, and morphology modification, which significantly improved its electrochemical performance and greatly enhanced the application potential of NVP in sodium-ion batteries.
[0005] The properties of the carbon layer are an important factor affecting the electronic conductivity of the Na3V2(PO4)3 / C material. However, the carbon layer coated in existing studies is amorphous carbon, which has limited effect on improving the electrochemical performance of the material. Therefore, in order to improve the rate performance and cycle stability of sodium-ion batteries under high current conditions and further promote the commercialization of sodium-ion batteries, it is necessary to develop an industrially applicable method for modifying sodium vanadium phosphate cathode materials. Summary of the invention
[0006] The purpose of the present invention is to solve the above-mentioned technical problems and to provide a modification method for nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material.
[0007] The modification method of nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material is achieved by the following steps:
[0008] 1. Weigh the sodium source, vanadium source, phosphorus source, nitrogen source and reducing agent according to the molar ratio;
[0009] 2. Mixing the sodium source, vanadium source, phosphorus source and nitrogen source to obtain a mixture, dispersing the mixture into a dispersion medium, and then performing high-energy ball milling at room temperature to obtain a slurry. After drying and grinding the slurry, a sodium vanadium phosphate (NVP) precursor material is obtained;
[0010] 3. The sodium vanadium phosphate precursor material is transferred to a tubular furnace, calcined at high temperature under Ar atmosphere protection, and then ground and sieved through a 400-mesh sieve to obtain a nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material (NVP / C / NC-TRI), thus completing the modification method.
[0011] Furthermore, in step 1, the sodium source is sodium carbonate; the vanadium source is vanadium pentoxide; the phosphorus source is ammonium dihydrogen phosphate; the nitrogen source is melamine; and the reducing agent is citric acid monohydrate.
[0012] Furthermore, the molar ratio of the sodium source, vanadium source, phosphorus source, nitrogen source and reducing agent in step 1 is 3:2:3:(1-3):(6-8).
[0013] Furthermore, the dispersion medium in step 2 is anhydrous ethanol.
[0014] Furthermore, the dispersion method in step 2 is electromagnetic stirring.
[0015] Furthermore, the mass volume ratio of the mixture to the dispersion medium in step 2 is 1 g: (5-7) ml.
[0016] Furthermore, the high-energy ball milling mixing is carried out at room temperature as described in step 2: at 20-25° C., at a speed of 400-600 r / min for 0.5 h, then taken out, and then the weighed reducing agent is added, and then the ball milling is continued at a speed of 400-600 r / min for 1.5 h to obtain a slurry.
[0017] Furthermore, the drying and grinding in step 2 are as follows: drying in a forced air drying oven at 80-120° C. for 12 hours, and then grinding in an agate mortar for 20-30 minutes.
[0018] Furthermore, the high temperature calcination in step three is divided into two stages of sintering. The first stage is pre-sintering, heating to 300-400°C at a rate of 4-8°C / min, and keeping warm for 6-10 hours. The second stage is sintering, heating to 750-850°C at a rate of 4-8°C / min, keeping warm for 6-10 hours, and then naturally cooling to room temperature.
[0019] The beneficial technical effects of the present invention are as follows:
[0020] 1. The present invention provides a method for modifying sodium vanadium phosphate positive electrode materials, wherein a nitrogen-containing carbon source is used to perform double carbon coating on the sodium vanadium phosphate positive electrode materials. Based on the coating of a single carbon source, the present invention introduces nitrogen doping to modify the surface of the material, and can form defects and active sites on the carbon skeleton. During the working process, electrons are effectively supplied to carbon atoms to effectively improve the electronic conductivity of the carbon layer, enhance the electronic conductivity of the coated carbon layer, realize rapid electronic conduction between particles, facilitate ion / electron exchange of active substances, greatly improve the performance of the positive electrode at a high rate, and the cycle performance, and the preparation is simple, easy to control, and the synthesis cycle is short, which has good application prospects.
[0021] 2. The present invention utilizes a high-temperature solid-phase sintering method to directly synthesize nitrogen-doped carbon source-modified Na3V2(PO4)3 positive electrode materials, which has the advantages of being simple and efficient, and provides a possible industrialization route; the sodium vanadium phosphate compound prepared by the present invention exhibits a high specific capacity, excellent cycle stability and rate performance as a positive electrode material in sodium ion batteries; the present invention has simple equipment and process flow, high product consistency, and is suitable for large-scale preparation of positive electrode material powders.
[0022] The invention is suitable for the modification of sodium vanadium phosphate positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD comparison diagram of NVP / C / NC-TRI material in the embodiment and existing NVP / C material;
[0024] Figure 2 This is the XPS graph of NVP / C / NC-TRI material in the embodiment;
[0025] Figure 3 This is a scanning electron microscope image of the existing NVP / C material in the embodiment;
[0026] Figure 4 This is a scanning electron microscope image of the NVP / C / NC-TRI material in the embodiment;
[0027] Figure 5 This is a transmission electron microscopy image of the carbon coating of NVP / C / NC-TRI material in the embodiment;
[0028] Figure 6 The initial charge-discharge curve comparison diagram of the NVP / C / NC-TRI material in the embodiment and the existing NVP / C material, wherein — represents the existing NVP / C material, and ﹎ represents the NVP / C / NC-TRI material;
[0029] Figure 7 The figure is a comparison of the rate performance of the NVP / C / NC-TRI material in the embodiment and the existing NVP / C material, wherein Indicates existing NVP / C materials, ■ indicates NVP / C / NC-TRI materials;
[0030] Figure 8 The 1C constant current cycling performance comparison diagram of the NVP / C / NC-TRI material in the embodiment and the existing NVP / C material is shown in FIG. Indicates existing NVP / C materials, ● indicates NVP / C / NC-TRI materials;
[0031] Fig. 9 The 10C constant current cycling performance comparison diagram of the NVP / C / NC-TRI material in the embodiment and the existing NVP / C material is shown in FIG. Indicates existing NVP / C materials, ◆ indicates NVP / C / NC-TRI materials;
[0032] Fig.10 This is a comparison spectrum of the AC impedance between the NVP / C / NC-TRI material in the embodiment and the existing NVP / C material, wherein ★ represents the existing NVP / C material, and ● represents the NVP / C / NC-TRI material. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0034] Specific implementation method 1: The modification method of the nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material in this implementation method is implemented by the following steps:
[0035] 1. Weigh the sodium source, vanadium source, phosphorus source, nitrogen source and reducing agent according to the molar ratio;
[0036] 2. Mix the sodium source, vanadium source, phosphorus source and nitrogen source to obtain a mixture, disperse it in a dispersion medium, and then perform high-energy ball milling at room temperature to obtain a slurry. After drying and grinding the slurry, a sodium vanadium phosphate precursor material is obtained;
[0037] 3. The sodium vanadium phosphate precursor material is transferred to a tubular furnace, calcined at high temperature under the protection of Ar atmosphere, and then ground and sieved through a 400-mesh sieve to obtain a nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material, thus completing the modification method.
[0038] The sodium vanadium phosphate precursor material obtained in step 2 of this embodiment is in the form of a blue powder.
[0039] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the sodium source in step 1 is sodium carbonate; the vanadium source is vanadium pentoxide; the phosphorus source is ammonium dihydrogen phosphate; the nitrogen source is melamine; and the reducing agent is citric acid monohydrate. The other steps and parameters are the same as those in specific implementation method 1.
[0040] Specific embodiment 3: This embodiment differs from specific embodiment 2 in that the molar ratio of the sodium source, vanadium source, phosphorus source, nitrogen source and reducing agent in step 1 is 3:2:3:(1-3):(6-8). Other steps and parameters are the same as those in specific embodiment 2.
[0041] Specific embodiment 4: This embodiment is different from specific embodiment 1 in that the dispersion medium in step 2 is anhydrous ethanol. The other steps and parameters are the same as those in specific embodiment 1.
[0042] Specific implementation method 5: This implementation method is different from specific implementation method 1 in that the dispersion method in step 2 is electromagnetic stirring. The other steps and parameters are the same as those in specific implementation method 1.
[0043] Specific embodiment 6: This embodiment is different from specific embodiment 1 in that the mass volume ratio of the mixture to the dispersion medium in step 2 is 1 g: (5-7) ml. The other steps and parameters are the same as those in specific embodiment 1.
[0044] Specific embodiment 7: This embodiment is different from specific embodiment 1 in that the high-energy ball milling mixing is performed at room temperature in step 2: the mixture is ball milled at 400-600 r / min for 0.5 h at 20-25° C., then taken out, and then the weighed reducing agent is added, and then the mixture is ball milled at 400-600 r / min for 1.5 h to obtain a slurry. The other steps and parameters are the same as those in specific embodiment 1.
[0045] Specific embodiment eight: This embodiment differs from specific embodiment one in that the drying and grinding in step two are: drying in a blast drying oven at 80-120°C for 12 hours, and then grinding in an agate mortar for 20-30 minutes. Other steps and parameters are the same as those in specific embodiment one.
[0046] Specific embodiment 9: This embodiment is different from specific embodiment 1 in that the high temperature calcination in step 3 is divided into two stages of sintering. The first stage is pre-sintering, heating to 300-400°C at a rate of 4-8°C / min, keeping warm for 6-10h, and the second stage is sintering, heating to 750-850°C at a rate of 4-8°C / min, keeping warm for 6-10h, and then naturally cooling to room temperature. The other steps and parameters are the same as those in specific embodiment 1.
[0047] Specific embodiment 10: This embodiment is different from specific embodiment 9 in that the high temperature calcination in step 3 is divided into two stages of sintering: the first stage is pre-sintering, the temperature is raised to 350°C at a rate of 5°C / min, and the temperature is kept for 8 hours; the second stage is sintering, the temperature is raised to 800°C at a rate of 5°C / min, and the temperature is kept for 8 hours, and then naturally cooled to room temperature. The other steps and parameters are the same as those of specific embodiment 9.
[0048] The beneficial effects of the present invention are verified by the following examples:
[0049] Example:
[0050] The modification method of nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material is achieved by the following steps:
[0051] 1. Weigh 0.7965 g of sodium carbonate, 0.9186 g of vanadium pentoxide, 1.7427 g of ammonium dihydrogen phosphate, 0.3185 g of melamine and 1.9249 g of citric acid monohydrate;
[0052] 2. The sodium carbonate, vanadium pentoxide, ammonium dihydrogen phosphate and melamine are mixed to obtain a mixture, which is then dispersed in 38 ml of anhydrous ethanol, and then subjected to high-energy ball milling at room temperature to obtain a slurry. After the slurry is dried and ground, a sodium vanadium phosphate (NVP) precursor material is obtained;
[0053] 3. The sodium vanadium phosphate precursor material is transferred to a tubular furnace, calcined at high temperature under Ar atmosphere protection, and then ground and sieved through a 400-mesh sieve to obtain a nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material (NVP / C / NC-TRI), thus completing the modification method.
[0054] The sodium vanadium phosphate precursor material obtained in step 2 of this embodiment is in the form of a blue powder.
[0055] The dispersion method in step 2 of this embodiment is electromagnetic stirring.
[0056] In step 2 of this embodiment, high-energy ball milling is performed at room temperature: at 25° C., the mixture is ball milled at a speed of 400 r / min for 0.5 h, then taken out, and the weighed reducing agent is added, and the mixture is ball milled at a speed of 400 r / min for 1.5 h to obtain a slurry.
[0057] The drying and grinding in step 2 of this embodiment are as follows: drying in a forced air drying oven at 80° C. for 12 h, and then grinding in an agate mortar for 20 min.
[0058] The high temperature calcination described in step three of this embodiment is divided into two stages of sintering. The first stage is pre-sintering, heating to 350°C at a rate of 5°C / min and keeping warm for 8h. The second stage is sintering, heating to 800°C at a rate of 5°C / min and keeping warm for 8h, and then naturally cooling to room temperature.
[0059] The NVP / C / NC-TRI material obtained in this embodiment is used as a positive electrode material for a sodium ion battery. It is mixed with a conductive agent (acetylene black) and a binder (PVDF) in a volume ratio of 7:2:1 to obtain a slurry, which is then coated on a metal aluminum current collector to obtain a positive electrode. Glass fiber is used as a separator, metal sodium is used as a counter electrode, 1 mol / L NaClO4 is used as an electrolyte, ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1 are used as solvents, and 5% fluoroethylene carbonate (FEC) is used as an additive. The sodium ion battery is assembled in a glove box filled with argon;
[0060] Control group: The existing NVP / C material was used to assemble the sodium-ion battery according to the above method.
[0061] The assembled sodium ion battery was left to rest for 12 hours and then subjected to constant current charge and discharge tests. The charge and discharge voltage window was 2.5-3.8V. The specific capacity, rate performance and long cycle performance of the positive electrode of the sodium ion battery were measured at room temperature.
[0062] The NVP / C / NC-TRI material obtained in this example was characterized and compared with the existing NVP / C material. Figure 1-4 As shown:
[0063] Figure 1 The XRD comparison diagram of NVP material before and after modification, that is, the XRD comparison diagram of NVP / C / NC-TRI material and existing NVP / C material, shows that the positions of all diffraction peaks before and after modification are consistent and belong to The space group is a rhombohedral phase structure and no impurity peaks are detected, indicating that the introduction of N has no effect on the crystal structure of the material.
[0064] Figure 2 This is the XPS diagram of NVP / C / NC-TRI material, indicating that N heteroatoms in NVP / C / NC-TRI material were successfully introduced into the surface carbon layer.
[0065] Figure 3 This is the morphology of the existing NVP / C material. The NVP / C material is an agglomerate composed of many irregular oblate spherical fine particles. The particle size is concentrated around 2.5μm, the particle size distribution is concentrated, and the particle size is uniform.
[0066] Figure 4 This is the morphology of NVP / C / NC-TRI material. The particle size of the samples synthesized by doping with different N-containing carbon sources is concentrated around 2μm. The NVP particles in the material do not form a simple accumulation, but are secondary particles formed by connecting small particles. The carbon material between the particles forms an effective conduction channel for electrons, thereby improving the electronic conductivity of the material.
[0067] Figure 5This is a transmission electron microscope image of carbon-coated NVP / C / NC-TRI material. The material is composed of micron-sized secondary particles formed by the agglomeration of primary particles of tens to hundreds of nanometers. The surface of the particles is covered with a thin carbon layer. A large number of primary particles are cross-linked with each other in the carbon array to form micron-sized secondary particles. The carbon layer on the surface of the material is completely and evenly coated, and the NVP particles are evenly dispersed in the carbon array.
[0068] The performance test results of the NVP / C / NC-TRI material and the existing NVP / C material after being assembled into sodium-ion batteries are shown in Figures 5 to 10:
[0069] Figure 6 It can be seen that the initial discharge specific capacity of the sodium ion battery made of NVP / C / NC-TRI material at a current density of 0.1C is increased from 100.2mAh / g to 103.5mAh / g.
[0070] Figure 7 It can be seen that the sodium ion battery made of NVP / C / NC-TRI material shows good rate performance. After cycling from 0.2C to 30C and then back to 0.2C, the discharge specific capacity can still be restored to the initial level, proving that the material has good reversibility.
[0071] Figure 8 It can be seen that the sodium ion battery made of NVP / C / NC-TRI material has an initial discharge specific capacity of 93.3mAh / g at a current density of 1C, and a capacity retention rate of up to 98.7% after 100 cycles, which shows good cycle stability.
[0072] Fig. 9 It can be seen that the sodium ion battery made of NVP / C / NC-TRI material has an initial discharge specific capacity of 94.5 mAh / g at 10C, and a capacity retention rate of 92.1% after 300 cycles, indicating the excellent stability of the modified material.
[0073] Fig.10 It can be seen that the modified sodium vanadium phosphate material has a higher diffusion rate.
[0074] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for modifying a nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material, characterized in that It is implemented as follows:
1. Weigh the sodium source, vanadium source, phosphorus source, nitrogen source and reducing agent according to the molar ratio; 2. Mix the sodium source, vanadium source, phosphorus source and nitrogen source to obtain a mixture, disperse it in a dispersion medium, and then perform high-energy ball milling at room temperature to obtain a slurry. After drying and grinding the slurry, a sodium vanadium phosphate precursor material is obtained; 3. The sodium vanadium phosphate precursor material is transferred to a tube furnace, calcined at high temperature under the protection of Ar atmosphere, and then ground and passed through a 400-mesh sieve to obtain a nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material, thus completing the modification method; wherein the sodium source in step 1 is sodium carbonate; the vanadium source is vanadium pentoxide; the phosphorus source is ammonium dihydrogen phosphate; the nitrogen source is melamine; and the reducing agent is citric acid monohydrate; The molar ratio of the sodium source, vanadium source, phosphorus source, nitrogen source and reducing agent in step 1 is 3:2:3:(1-3):(6-8); The dispersion medium in step 2 is anhydrous ethanol; The dispersion method in step 2 is electromagnetic stirring; The mass volume ratio of the mixture to the dispersion medium in step 2 is 1 g: (5-7) ml; The high-energy ball milling mixing is performed at room temperature as described in step 2: at 20-25° C., at a speed of 400-600 r / min for 0.5 h, then taken out, and then the weighed reducing agent is added, and then the ball milling is continued at a speed of 400-600 r / min for 1.5 h to obtain a slurry; Drying and grinding in step 2: drying in a forced air drying oven at 80-120° C. for 12 h, and then grinding in an agate mortar for 20-30 min; The high temperature calcination in step three is divided into two stages of sintering. The first stage is pre-sintering, heating to 300-400°C at a rate of 4-8°C / min, keeping warm for 6-10h, and the second stage is sintering, heating to 750-850°C at a rate of 4-8°C / min, keeping warm for 6-10h, and then naturally cooling to room temperature.
2. The method for modifying the nitrogen-doped carbon double-coated sodium vanadium phosphate positive electrode material according to claim 1, characterized in that The high temperature calcination in step three is divided into two stages of sintering. The first stage is pre-sintering, heating to 350°C at a rate of 5°C / min and keeping warm for 8h. The second stage is sintering, heating to 800°C at a rate of 5°C / min and keeping warm for 8h, and then naturally cooling to room temperature.
Citation Information
Patent Citations
Preparation method of carbon-nitrogen co-coated sodium vanadium phosphate positive electrode material for sodium-ion batteries
CN107706392A